Iranian strategy towards the Arab region - حسون, عبد العزيز; حيدر , عفيف; لايقه , رامي (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research confirms the great importance of the Arab region to the Islamic Republic of Iran and its constant concern for Keeping distinct interests within this vital region, and the research reviews the definition of the strategy in general and foundations Iranian strategy in the Arab region, and focus on the most important factors related to implementing the Iranian strategy in Arab region by dividing it into local, regional and international factors, and the research focuses on the most important trends taken from Before Iran towards the Arab region by reviewing the Iranian project in the region, especially after the eleventh events From September and the events that followed, and the tools and mechanisms that depend on them, the research also focuses specifically on the situation The Iranian is one of the crises in the Arab region, especially in Syria, and its impact on its political position and weight. The research reached many results and made some recommendations.